Literature Review : Hubungan Kualitas Udara Indoor terhadap Kejadian Sick Building Syndrome pada Pekerja Perkantoran - Nanda Ika Vera Marlina; Onny Setiani; Tri Joko (Fakultas Teknik, 2023)
Indoor air quality includes poor physical, chemical and biological quality which can have a negative impact on workers in the form of complaints of health problems or Sick Building Syndrome (SBS). This study aims to analyze the relationship between indoor air quality and the incidence of Sick Building Syndrome in Offices. Article searches were carried out through the journal sites Science Direct, Scopus, Semantic Scholar, Google Scholar, and nature. The selection of articles was carried out with the following criteria: open access full text, publication 2010-2022, articles in English, suitability of the dependent and independent variables. Based on 53 relevant articles, 5 main articles met the criteria and were discussed further in this study. The 5 main articles show the results of the statistical test p-value 0.05, which means there is a significant relationship between temperature, humidity, bad air such as dusty, stuffy, dry air and bad smell, increased exposure to CO2, ventilation quality, and light intensity with the incidence of Sick Building Syndrome (SBS) in office workers which includes sneezing, skin redness, eye pain, sore eyes and itchy eyes, dizziness, headache, nausea, nose irritation, dry throat, dyspnea, bad taste, feeling unwell, sneezing, bad mood, motivation, and concentration problems.